2013
DOI: 10.4028/www.scientific.net/amm.275-277.1866
|View full text |Cite
|
Sign up to set email alerts
|

Property Study on High-Speed Steel Deposited TiN Coatings by Magnetron Sputter Ion Plating

Abstract: TiN coatings were deposited by Magnetron Sputter Ion Plating (MSIP) on the surface of high-speed steel W18Cr4V.The microstructure,coating thickness, micro-hardness and wear resistance of surface modification sample were investigated by the D/MAX-ⅢB X-ray diffraction tester, the coating thickness tester, the HV-1000 micro-sclerometer,the LKDM-2000 friction and wear tester,the S-3000N scaning electron microscopy.The influence of sputtering time,N2 partial pressures and sputtering current on the microstructure,co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Magnetron sputtering technology is a kind of thin films deposition technology widely used at present due to its high sputtering rate, good binding force for thin films pasting on the substrate, stable device performance, convenient operating control system and low temperature on the substrate and so on [3][4][5][6]. Many researches have demonstrated that the magnetron sputtering deposition technology can effectively improve the surface properties of the materials [7][8][9][10][11]. Chen and Zhang have studied the influence of the TiN films on high-speed steel and hard alloy [10][11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Magnetron sputtering technology is a kind of thin films deposition technology widely used at present due to its high sputtering rate, good binding force for thin films pasting on the substrate, stable device performance, convenient operating control system and low temperature on the substrate and so on [3][4][5][6]. Many researches have demonstrated that the magnetron sputtering deposition technology can effectively improve the surface properties of the materials [7][8][9][10][11]. Chen and Zhang have studied the influence of the TiN films on high-speed steel and hard alloy [10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have demonstrated that the magnetron sputtering deposition technology can effectively improve the surface properties of the materials [7][8][9][10][11]. Chen and Zhang have studied the influence of the TiN films on high-speed steel and hard alloy [10][11]. Results demonstrated that the deposition time has influence on the surface properties of the materials, but has not been clarified the influencing mechanisms of the deposition time on material property [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation